Effect of Testosterone on Lead Acetate Toxicity in Male Albino Rats - Mahmood, Nazar Mohammed Shareef; Hamad, Sarkawt Hamad Ameen; Hassan, Dlshad Hussein; Othman, Karwan Ismael (Kurdistan Journal of Applied Research, 2017)
The toxicity of lead acetate (L. A.) concerned to public health disruptor due to its persistence in the environment and it has the adverse influence on the human and animal health as well. It causes physiological,biochemical, and neurological dysfunctions in humans. Histologically it has a negative effect on the liver which is considered one of the major target organs where acts as detoxification machine by elimination the toxic substance from the blood in rich with it. As well as it affects kidneys that are the two of the most filtering organs. Therefore the present study was aimed to investigate the histopathological effect of L.A. on liver and kidney tissues in male rats. Twenty male rats involved in the study were equally and randomly divided into two groups each of them involved 10 animals. Group I (castrated rats) and Group II (control) each group received 80mg/L of lead acetate dissolved in one liter distilled water by drinking for 15 days. Histological sections showed some alterations including abnormal architecture, cell degeneration, nuclear degeneration, hyperchromatic hepatocytes, immune cells, degeneration in tubules, dilation in sinusoids, dilation in central vein of liver increased bowman’s space glomerular atrophy degeneration of tubular cells in liver and kidney tissues of rats in castrated rats from control group. But the size of degenerated tissue was more severe in castrated male rats. It was concluded that the castration process could produce a hypogonadism and decreased testosterone which owns many receptors in kidney and liver may produce adverse influence with L.A. administration.